HIERARCHICAL MODEL FOR ALTERNATIVE METHODS COMPARISON OF THE CIVIL PROTECTION ANALYSIS AND INFORMATION SYSTEM OPERATION - Barylo O.G. (Pressing Problems of Public Administration, 2017)
The paper raises the problem of ef cient managerial decision-making on the basis of timely, relevantand reliable information. The system of indicators has been proposed, and a hierarchical model foralternative methods comparison of the Civil Protection Analysis and Information System operationhas been built on the basis of the method of hierarchy analysis. The methodology for estimating themethods of the Civil Protection Analysis and Information System operation and the calculation taskhave been developed.